Quantum chemical strain analysis for mechanochemical processes - Neudecker, Tim; Dreuw, Andreas (Accounts of chemical research, 2017)
The use of mechanical force to initiate a chemical reaction is an efficient alternative to the conventional sources of activation energy, i.e., heat, light, and electricity. Applications of mechanochemistry in academic and industrial laboratories are diverse, ranging from chemical syntheses in ball mills and ultrasound baths to direct activation of covalent bonds using an atomic force microscope. The vectorial nature of force is advantageous because specific covalent bonds can be preconditioned for rupture by selective stretching. However, the influence of mechanical force on single molecules is still not understood at a fundamental level, which limits the applicability of mechanochemistry. As a result, many chemists still resort to rules of thumb when it comes to conducting mechanochemical syntheses. In this Account, we show that comprehension of mechanochemistry at the molecular level can be tremendously advanced by quantum chemistry, in particular by using quantum chemical force analysis tools.